The feasibility and diagnostic value of intravoxel incoherent motion diffusion-weighted imaging in the assessment of myocardial fibrosis in hypertrophic cardiomyopathy patients. Issue 132 (November 2020) - Wu, Rui; An, Dong-Aolei; Shi, Ruo-Yang; Chen, Bing-hua; Wu, Chong-Wen; Jiang, Meng; Xu, Jian-Rong; Wu, Lian-Ming; Pu, Jun
Highlights: IVIM DW-CMR can be used for patients with renal insufficiency. IVIM DW-CMR may help clinicians to detect myocardial fibrosis. D, D* and f show significant associations with ECV and contractile function. Abstract: Purpose: To investigate the feasibility and diagnostic value of intravoxel incoherent motion (IVIM) in the assessment of myocardial fibrosis in hypertrophic cardiomyopathy (HCM) patients. Methods: Fifty-five HCM patients underwent IVIM diffusion-weighted cardiovascular resonance imaging; Cine, T1 mapping, IVIM and late gadolinium enhancement (LGE) were performed. The relationship of strain, pre T1, extracellular volume (ECV), IVIM-derived parameters (D, D* and f) and LGE were analyzed based on 16 American Heart Association segments. Abnormal segments of myocardial fibrosis were defined as: the presence of LGE (LGE+) or ECV ≥ 29.6 %. Results: D parameter was significantly increased in LGE + vs LGE- (1.89 ± 0.14 μm 2 /ms vs. 1.63 ± 0.12 μm 2 /ms, p < 0.001) and ECV ≥ 29.6 % vs ECV < 29.6 % (1.84 ± 0.13 μm 2 /ms vs. 1.61 ± 0.12 μm 2 /ms, p < 0.001), respectively. D* and f parameters were significantly decreased in LGE + vs LGE- (D*: 34.9 ± 6.6 μm 2 /m vs 55.2 ± 11.4 μm 2 /m, p < 0.001; f: 10.8 ± 1.29 % vs 12.5 ± 1.26 %, p < 0.001) and ECV ≥ 29.6 % vs ECV < 29.6 % (D*: 37.5 ± 6.9 μm 2 /m vs 59.6 ± 9.2 μm 2 /m, p < 0.001; f: 10.9 ± 1.1 % vs 13.00 ± 1.0 %, p = 0.021), respectively. Moreover, significant correlations were demonstrated between D and ECV, as well as D* and f. Conclusions: : IVIM DW-CMR has proven to be ingenious in the investigation of myocardial fibrosis; D* and f parameters may have potential value to assess the perfusion status of fibrotic regions in HCM patients.